2021
DOI: 10.1002/aur.2481
|View full text |Cite
|
Sign up to set email alerts
|

Differential Item Functioning Based on Autism Features, IQ, and Age on the Screen for Child Anxiety Related Disorders (SCARED) Among Youth on the Autism Spectrum

Abstract: Anxiety commonly occurs among youth on the autism spectrum, yet measurement of anxiety in this population is complicated by a number of factors, including potentially overlapping symptomatology, the child's intellectual functioning, and changes in anxiety across development. Moreover, few studies have examined the psychometric properties of anxiety measures in this population, and no study to date has tested whether there are systematic differences in the measurement of anxiety, or differential item functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…In addition, there may be confounders that were not considered in our analyses like the child’s intellectual as well as adaptive functioning, comorbidities, and changes in anxiety across development. There is evidence that these factors affect the development and intensity of MAD symptomatology also in individuals with ASD ( Ben-Itzchak et al, 2020 ; Schiltz & Magnus, 2021 ). Therefore, future investigations should include samples comprising a broader range of thoroughly surveyed data on symptomatology and should also consider confounders like age and IQ, allow for gender differentiations as well as for other potential confounders such as comorbidity or other medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there may be confounders that were not considered in our analyses like the child’s intellectual as well as adaptive functioning, comorbidities, and changes in anxiety across development. There is evidence that these factors affect the development and intensity of MAD symptomatology also in individuals with ASD ( Ben-Itzchak et al, 2020 ; Schiltz & Magnus, 2021 ). Therefore, future investigations should include samples comprising a broader range of thoroughly surveyed data on symptomatology and should also consider confounders like age and IQ, allow for gender differentiations as well as for other potential confounders such as comorbidity or other medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest TEN treatment could have a cumulative effect on improving anxiety in ASD. Although the questionnaire demonstrated a positive response to treatment, questionnaires are subjective, and studies have shown that they do not capture anxiety differences equivalently for all individuals with ASD [70]. More objective measurements of anxiety would improve future studies.…”
Section: Ten Improved Rating Of Anxiety In Asdmentioning
confidence: 99%
“…That is, it may be difficult to distinguish between an instrument's target construct (e.g., anxiety) and autistic traits or related behaviors that could be but are not necessarily related to that construct (e.g., repetitive behavior or fidgeting). For example, measures intended to capture autism traits may be elevated among children with more externalizing behavior and lower language and cognitive skills (Hus et al, 2013) and that responses on measures of anxiety may be impacted by autism characteristics (Schiltz & Magnus, 2021). As another example, an item on a sensory reactivity questionnaire about avoiding noisy parties may be influenced by the respondent's social motivation or social anxiety.…”
Section: Current Issues In Autism Prom Researchmentioning
confidence: 99%
“…Others have used a community based participatory research approach with autistic adults to adapt existing instruments for use with autistic participants (Nicolaidis et al, 2020). Other approaches include the application of methods such as item response theory (IRT), structural equation modeling, and network analysis, and even more standard approaches such as test–retest and convergent validity to answer substantive empirical questions about the psychometric properties of both newly‐created and existing PROMs in the autistic population (e.g., Frazier et al, 2022; Mazefsky, Yu, et al, 2018; Schiltz et al, 2019; Schiltz & Magnus, 2020, 2021; Uljarević et al, 2022; Williams et al, 2021; Williams, Cascio, & Woynaroski, 2023). Still others have begun to incorporate PROMs into routine clinical practice, and the first systems of measurement‐based care (Lewis et al, 2018) were recently described within autism research (McFayden et al, 2021; Schwartzman et al, 2023).…”
Section: Progress On Proms In Autism Researchmentioning
confidence: 99%